Isolated Abducens Nerve Palsy: A Case Report of Cerebral Pseudocyst of Dorello’s Canal - Puspitasari, Vivien; Japutri, Josephine; Solansa, Tracy; Cenweikiawan, Anderson (Fakultas Kedokteran Universitas Pelita Harapan, 2024)
Background: Abducens nerve is the second longest intracranial path out of all of the cranial nerves. Abducens nerve pasly had a prevalence 11.3/100.000 and mostly seen in adults. Isolated abducens nerve palsy due to neoplastic lesion are rare and mostly related to skull base tumor.Case Presentation: We present a case of 57 years old woman with complaints of red right eye and worsening headache associates with diplopia on the right lateral gaze for three days prior admission. She was later diagnosed with isolated abducens nerve palsy associated to neoplasm cause in Dorello’s canal. Patient was then discharged with symptomatic therapy and educated for head posturing and avoid triggers.Conclusions: Abducens nerve palsy is the most common isolated ocular nerve palsy. The incidence of mass formation such as neoplastic lesion or cyst are rare.